Developing an improved vaccine against tuberculosis. - Mcshane, H (2004)
Despite the availability of a vaccine for over 80 years, the tuberculosis epidemic continues to be a major cause of mortality and morbidity throughout the world. The factors contributing to the resurgence of tuberculosis and the possible explanations for the failure of the current vaccine, bacille Calmette-Guérin, are discussed. The nature of protective immunity to Mycobacterium tuberculosis and how this relates to the development of new candidate vaccines is then considered. The issues surrounding the progression of the most promising candidates into Phase I clinical trials are also discussed.